Fluorite synthetic stone and method for manufacturing fluorite synthetic stone

By using fluorite synthetic stone with high CaF2 content in steel production, the problems of unstable supply of natural fluorite and low impurity removal efficiency are solved, and efficient impurity removal and slag fluidity are achieved.

CN119156355APending Publication Date: 2024-12-17MEXICHEM FLUOR S A DE CV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380037481.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-06
Filing Date
2023-05-04
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The supply of natural fluorostone in steel production is uncontrolled, resulting in supply chain safety risks, and existing slag additives are limited in efficiency in removing impurities from steel.

Method used

New methods of formulation and sintering are used to manufacture fluorite synthetic stones with high CaF2 content, and by dispersing CaF2 crystals in glass substrates, forming a composite structure for steelmaking and other applications, reducing the viscosity of the slag and improving the ability to remove impurities.

Benefits of technology

The wear resistance, compressive strength and water absorption are achieved comparable to or better than natural stone, and are almost free of carbon, sulfur and phosphorus impurities, which improve the fluidity of the slag and the impurity removal efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119156355A_ABST
    Figure CN119156355A_ABST
Patent Text Reader

Abstract

A fluorite synthetic stone comprises: (a) a glass matrix containing Ca, Si, and O and having a predetermined weight ratio of Ca to Si; and (b) CaF2 crystals dispersed in the glass matrix at a concentration of at least about 70 wt.%. A method of making a fluorite synthetic stone includes formulating a particulate mixture comprising: CaF2 crystals at a concentration of at least about 70 wt.%; and an excipient having a predetermined weight ratio of Ca to Si. An aggregate is prepared from the mixture of particles. The aggregate is heat treated to form a plurality of fluorite synthetic stones, where each synthetic stone comprises: a glass matrix comprising Ca, Si, and O; and CaF2 crystals dispersed in the glass matrix at a concentration of at least about 70 wt.%.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Related Applications

[0002] This patent document claims priority under 35 U.S.C. 119(e) to U.S. Provisional Patent Application No. 63 / 339,019, filed on May 6, 2022, which is incorporated herein by reference in its entirety. Technical Field

[0003] The present disclosure relates generally to slag additives for the steel industry, and more particularly to fluorite synthetic stone. Background Art

[0004] The refining process in steel production is carried out by injecting oxygen and is an intensive process. Reactions occur in the hot metal, but there are also some other reactions that occur at the slag-metal interface or the slag-gas interface. The interaction of the slag and the gas produces a "foam". The viscosity controls the characteristics of the foam. Secondary refining of steel aims to reduce carbon, sulfur and phosphorus impurities to very low levels. The slag floats on the molten metal, protects the surface from oxidation, and absorbs impurities dissolved in the molten metal. The typical composition of slag is rich in CaO, with some MgO added. Fluorospar, a mineral containing CaF2, can be used as a slag additive or flux to enhance the removal of impurities such as sulfur and phosphorus from the molten metal and / or to enhance the fluidity of the slag. However, dependence on fluorospar, a natural stone product with an uncontrolled supply, can put the supply chain at risk. BRIEF DESCRIPTION OF THE DRAWINGS

[0005] Figure 1 is a flow chart of an exemplary method of producing fluorite synthetic stone.

[0006] Figure 2 is a photograph of an exemplary fluorite synthetic stone.

[0007] Figure 3A and 3B Portions of the x-ray diffraction patterns of aggregate (green sample) and synthetic stone (sintered sample) prepared from a blend of concentrating fluorspar and sludge having a Ca to Si weight ratio of about 2:1 are shown, respectively. DETAILED DESCRIPTION

[0008] A fluorite synthetic stone having a high CaF2 content and stone-like properties for steelmaking and other applications is described in the present disclosure. The fluorite synthetic stone manufactured using a novel method including formulation, aggregation and sintering has a composite structure comprising CaF2 crystals dispersed in a glass matrix comprising Ca, Si and O at a concentration of at least about 70wt.% (and usually higher). When prepared under suitable process conditions with a predetermined weight ratio of Ca to Si, the fluorite synthetic stone may include an intergranular (matrix) phase surrounding the CaF2 crystals, which is believed to contribute to the excellent performance of the synthetic stone product. For example, the synthetic stone may exhibit wear resistance, compressive strength and / or water absorption comparable to or superior to that of natural stone. The manufacturing process may be controlled so that the fluorite synthetic stone contains little or no carbon, sulfur and / or phosphorus impurities that may be harmful to steelmaking. The synthetic stone may be added to a steelmaking furnace containing molten steel and slag to reduce the viscosity of the slag and / or increase the ability of the slag to remove impurities (e.g., sulfur) from the molten steel. Typically, 2-10 kg of fluorite synthetic stone can be added per ton of steel.

[0009] Before describing fluorite synthetic stone in detail, refer to Figure 1 A method for making a synthetic stone is explained. It should be noted that the terms "fluorite synthetic stone" and "synthetic stone" are used interchangeably throughout the disclosure. In general, method 100 includes formulating 102 a particle mixture, the particle mixture containing (a) CaF2 crystals at a concentration of at least about 70wt.%, and (b) an excipient having a predetermined weight ratio of Ca to Si. Aggregates are then prepared 104 from the particle mixture, and the aggregates are heat treated 106 to form a plurality of fluorite synthetic stones, each of which has a composite structure comprising: a glass matrix containing Ca, Si and O; and CaF2 crystals dispersed in the glass matrix at a concentration of at least about 70wt.%. More specifically, the glass matrix can contain Ca and Si in a predetermined weight ratio, as described below.

[0010] The preparation 102 of the particle mixture may include a number of steps, such as Figure 1 As shown. First, 108 particulate material can be obtained from a mining operation. This may require collecting fluorspar and low-grade materials such as sludge, tailings, and slime from the mining operation, and then drying and / or screening as needed to obtain the particulate material. Various grades of fluorspar may be suitable. For example, the fluorspar may be acid grade or concentrating fluorspar that has been concentrated to 97%+CaF2. Alternatively, non-compliant acid grade fluorspar containing about 90% CaF2 may be used.

[0011] The chemical content of the particulate material is then determined 110. Of particular interest are the concentrations of Ca, F, and Si, which can be used to estimate the amount of CaF2, SiO2 CaO, and / or CaCO3 in the particulate material. The chemical content 110 can be determined using chemical analysis methods such as x-ray fluorescence (XRF), which is capable of determining the concentration of elements heavier than oxygen when using appropriate instrumentation.

[0012] Once the chemical content is known, selected portions of the particulate material are combined 112 to form the above-described particulate mixture. It will be appreciated that the excipient comprises Ca, Si, and O, with little or no unwanted impurities, such as S and P. Preferably, the excipient comprises S at a concentration of less than about 0.1 wt.% and / or is free of S; additionally or alternatively, the excipient preferably comprises P at a concentration of less than about 0.1 wt.% and / or is free of P. Any C present in the excipient is substantially or completely removed during downstream processing steps (heat treatment). For certain applications, it may be beneficial to have additional ceramic components in the fluorite synthetic stone product, and one or more additional particulate materials such as Al2O3 and / or MgO may be added to the particulate mixture at this point in the process in desired amounts.

[0013] Aggregate is then prepared 104 from the particle mixture, for example by mixing a binder into the particle mixture, and then forming the aggregate by granulation, compaction, extrusion, micronization, briquetting and / or another forming method. For example, granulation can be performed in a rotating drum / rotating disk to form aggregate, or a briquetting machine or extruder can be used. The size of the aggregate can be a linear dimension (width or diameter) ranging from a few millimeters to a few centimeters. The binder added to the particle mixture can include an organic binder, an inorganic binder and / or an aqueous binder. In an example, the binder can include a sodium silicate solution (water glass). Typically, the binder is added to the particle mixture in an amount of about 0.5wt.% to about 10wt.%, or about 5wt.% to about 7wt.%.

[0014] In some examples, the aggregate is dried prior to further processing to improve its green strength. Drying of the aggregate may include evaporating or curing the binder and may be performed passively (e.g., in air) or actively (e.g., in an oven at a suitable temperature).

[0015] To achieve sintering and decarburization, the aggregate is subjected to a heat treatment 106. Formed in the heat treatment 106 are a variety of sintered synthetic stones, such as Figure 2As shown, each fluorite synthetic stone comprises CaF2 crystals dispersed in a glass matrix comprising Ca, Si and O at a concentration of at least about 70wt.%. More typically, the concentration of CaF2 crystals is 80wt.% or higher, or 90wt.% or higher. In some instances, CaF2 crystals may be present in a concentration of at least about 92wt.%, or at least about 94wt.% and / or up to 96wt.%. Under heat treatment conditions, an excipient having a predetermined ratio of Ca to Si forms a glass matrix that at least partially surrounds the CaF2 crystals. In addition, the CaCO3 present in the excipient may be decomposed into CO2 gas and CaO, which may be combined with silicon. Heat treatment may be performed at a temperature of at least about 950°C or at least about 1000°C. Typically, the temperature is not higher than about 1200°C and / or lower than the melting temperature of CaF2. The duration of heat treatment may be at least about 20 minutes, at least about 40 minutes, or at least about 60 minutes and / or at most about 120 minutes. Heat treatment can be carried out until CaCO3, CaO and / or SiO2 crystals are no longer detectable by x-ray diffraction (XRD), and / or the carbon content is less than 1wt.%. In some instances, as described below, the excipient may include excessive Si, and therefore the SiO2 peak may not completely disappear from the XRD diagram. Preferably, the CaCO3 and / or CaO peak completely disappear. Heat treatment may require furnace heating or microwave heating. Heat treatment can be carried out in air. In the latter case, before microwave heating, the aggregate can be embedded in a susceptor material such as carbon.

[0016] The glass matrix of the fluorite synthetic stone may contain one or more silicates and / or oxides, such as Ca-Si-O compounds (e.g., Ca2SiO3 and / or Ca2SiO4 (2CaO·SiO2)), Si-O compounds (e.g., SiO2), and / or Ca-O compounds (e.g., CaO). The glass matrix may be partially or completely amorphous (non-crystalline). Therefore, in some instances, the glass matrix may be at least partially crystalline. It is also contemplated that under some processing conditions, the glass matrix may be completely crystalline. Preferably, the synthetic stone contains less than about 1 wt.% of free CaO (i.e., CaO that is not part of the Ca-Si-O compound) and other hygroscopic phases to reduce the water absorption of the synthetic stone. The glass matrix may be partially fluorinated. Due to decarburization during heat treatment, the amount of carbon in the sintered synthetic stone may be less than about 1 wt.%, less than about 0.1 wt.%, and / or preferably below the detectable limit of the measurement method.

[0017] In order to obtain the desired glass matrix, the predetermined weight ratio of Ca to Si in the excipient is preferably greater than 1, such as from about 2: 1 to about 4: 1. At a Ca to Si ratio within this range, the fluorite synthetic stone produced upon sintering may include an amorphous intergranular phase at least partially surrounding the CaF2 crystals. The amorphous intergranular phase (i.e., the glass matrix) may include Ca and Si in a predetermined weight ratio (e.g., greater than 1, or from about 2: 1 to about 4: 1), and may contribute to the excellent mechanical integrity and low water absorption of the fluorite synthetic stone.

[0018] For certain applications, the excipient may include a Ca to Si weight ratio equal to or less than 1 (e.g., 0.4:1 to 1:1). At lower Ca / Si ratios, in addition to CaF2 crystals, the fluorite synthetic stone may also include a Si-containing crystalline phase, such as SiO2, dispersed in the glass matrix. Although higher amounts of Si (or lower Ca to Si weight ratios) may hinder sintering, the resulting fluorite synthetic stone may have increased compressive strength values ​​due to the presence of the Si-containing crystalline phase. At lower Si contents (e.g., Ca:Si>4:1), the water absorption of the fluorite synthetic stone produced by the method may be unfavorably increased due to residual free CaO in the sintered stone. As described above, the fluorite synthetic stone preferably contains a limited amount of free CaO.

[0019] Figure 3A and 3B Portions of the x-ray diffraction patterns of aggregate (green sample) and synthetic stone (sintered sample) prepared from a blend of selected fluorspar and sludge with a Ca to Si weight ratio of about 2 are shown, respectively. The sintered sample was heat treated at 1200°C for 60 minutes. It can be seen that Figure 3A The peaks corresponding to crystalline SiO2 and CaCO3 are Figure 3B In the absence of, indicating amorphization during heat treatment. Figure 3B A new low-intensity peak (indicated by the arrow) that may correspond to a glassy silicate phase (e.g., CaSiO3) is observed.

[0020] The CaF2 crystals in the fluorite synthetic stone may have a linear size (e.g., length and / or width) in the range of about 500nm to about 500 microns, or more typically about 1 micron to about 150 microns. The CaF2 crystals may have a multimodal size distribution in the glass matrix. As discussed above with respect to the Ca:Si ratio, in some instances, the synthetic stone may further include SiO2 crystals dispersed in the glass matrix. Additionally or alternatively, the synthetic stone may include additional ceramic components dispersed in the glass matrix, such as Al2O3 crystals and / or MgO crystals. These optional additional ceramic crystals may have a linear size within the range described above for the CaF2 crystals, and / or they may have a multimodal size distribution. Due to the increased temperature of the heat treatment, the binder present in the aggregate may be pyrolyzed or evaporated, and therefore the fluorite synthetic stone may not contain a binder (e.g., an organic or aqueous binder). In other instances, such as when an inorganic binder is used, the binder may undergo a chemical transformation during the heat treatment and remain in the synthetic stone product in a transformed chemical state.

[0021] During the heat treatment, the porosity in the aggregate is significantly reduced, and the resulting sintered synthetic stone may include primarily or only closed pores. The fluorite synthetic stone may have a buoyancy test based on the Archimedean principle of about 2.2 g / cm 3 About 3g / cm 3 The sintered stone may have a nominal linear dimension (width or diameter) in the range of a few millimeters to a few centimeters.

[0022] Fluorite synthetic stones prepared as described herein can exhibit features and properties comparable to or superior to those of natural stones. For example, the synthetic stone can exhibit high wear resistance when subjected to a drum test for 60 minutes; the mass loss of the sample can be about 7 wt.% or less. Preliminary experiments indicate that the synthetic stone can withstand an average compressive force of at least about 1330 N before breaking. The synthetic stone can also or alternatively exhibit a water absorption of no more than about 0.1 wt.% after six days in a humidity chamber (>90% relative humidity).

[0023] The subject matter of the present disclosure may relate to, among other things:

[0024] A first aspect relates to a fluorite synthetic stone comprising: a glass matrix containing Ca, Si and O and having a predetermined weight ratio of Ca to Si; and CaF2 crystals dispersed in the glass matrix at a concentration of at least about 70 wt.%.

[0025] A second aspect relates to the fluorite synthetic stone according to the first aspect, wherein the predetermined Ca to Si weight ratio is greater than 1, and / or wherein the predetermined Ca to Si weight ratio is from about 2:1 to about 4:1.

[0026] A third aspect relates to the fluorite synthetic stone according to any of the preceding aspects, wherein the predetermined weight ratio of Ca to Si is less than 1.

[0027] A fourth aspect relates to a fluorite synthetic stone according to any preceding aspect, wherein the concentration is at least about 80 wt.%, at least about 90 wt.%, at least about 92 wt.%, or at least about 94 wt.%, and / or up to about 96 wt.%.

[0028] A fifth aspect relates to a fluorite synthetic stone according to any of the preceding aspects, wherein the glass matrix comprises one or more silicates and / or oxides.

[0029] A sixth aspect relates to the fluorite synthetic stone according to the fifth aspect, wherein the glass matrix contains a Ca-Si-O compound selected from the group consisting of Ca2SiO3 and Ca2SiO4 (2CaO·SiO2).

[0030] A seventh aspect relates to a fluorite synthetic stone according to any of the preceding aspects, wherein the glass matrix is ​​partially fluorinated.

[0031] An eighth aspect relates to the fluorite synthetic stone according to any preceding aspect, comprising free CaO at a concentration of less than about 1 wt.%.

[0032] A ninth aspect relates to a fluorite synthetic stone according to any preceding aspect, wherein the CaF2 crystals have a linear dimension in the range of about 500 nm to about 500 microns.

[0033] The tenth aspect relates to the fluorite synthetic stone according to the ninth aspect, wherein the linear dimension is in the range of about 1 micron to about 150 microns.

[0034] An eleventh aspect relates to a fluorite synthetic stone according to any preceding aspect, wherein the CaF2 crystals have a multimodal size distribution.

[0035] A twelfth aspect relates to the fluorite synthetic stone according to any of the preceding aspects, further comprising SiO2 crystals dispersed in the glass matrix.

[0036] A thirteenth aspect relates to the fluorite synthetic stone according to any of the preceding aspects, further comprising Al2O3 crystals and / or MgO crystals dispersed in the glass matrix.

[0037] A fourteenth aspect relates to a fluorite synthetic stone according to any of the preceding aspects, comprising C at a concentration of less than about 1 wt.% and / or containing no C.

[0038] A fifteenth aspect relates to a fluorite synthetic stone according to any of the preceding aspects, comprising CaCO3 at a concentration of less than about 2 wt.% and / or containing no CaCO3.

[0039] A sixteenth aspect relates to the fluorite synthetic stone according to any of the preceding aspects, which comprises S at a concentration of less than about 0.1 wt.% and / or contains no S.

[0040] A seventeenth aspect relates to the fluorite synthetic stone according to any of the preceding aspects, which comprises P at a concentration of less than about 0.1 wt.% and / or contains no P.

[0041] An eighteenth aspect relates to the fluorite synthetic stone according to any of the preceding aspects, which does not contain a binder.

[0042] A nineteenth aspect relates to a fluorite synthetic stone according to any of the preceding aspects, having a buoyancy test as determined by the Archimedean principle at about 2.2 g / cm 3 About 3g / cm 3 density within the range of .

[0043] A twentieth aspect relates to the fluorite synthetic stone according to any of the preceding aspects, which has high wear resistance, wherein after subjecting a sample of the fluorite synthetic stone to a drum test for 60 minutes, the mass loss of the sample is about 7 wt.% or less.

[0044] A twenty-first aspect relates to a fluorite synthetic stone according to any preceding aspect, which withstands an average compressive force of at least about 1330N before failure.

[0045] A twenty-second aspect relates to a fluorite synthetic stone according to any preceding aspect, which exhibits a water absorption of no more than about 0.1 wt. % after six days in a humidity chamber (>90% relative humidity).

[0046] A twenty-third aspect relates to a fluorite synthetic stone according to any preceding aspect, having a nominal size in the range of a few millimeters to a few centimeters.

[0047] A twenty-fourth aspect relates to a method of using the fluorite synthetic stone according to any of the preceding aspects, the method comprising: adding a plurality of fluorite synthetic stones to a steelmaking furnace containing slag and molten steel.

[0048] A twenty-fifth aspect relates to the method according to the preceding aspect, wherein the addition of the fluorite synthetic stone reduces the viscosity of the slag.

[0049] A twenty-sixth aspect relates to the method according to any preceding aspect, wherein the addition of the fluorite synthetic stone increases the ability of the slag to remove sulfur from the molten steel.

[0050] The twenty-seventh aspect relates to a method for manufacturing fluorite synthetic stone, the method comprising: preparing a particulate mixture, the particulate mixture comprising: CaF2 crystals having a concentration of at least about 70 wt.%; and an excipient having a predetermined weight ratio of Ca to Si; preparing an aggregate from the particulate mixture; and heat treating the aggregate to form a plurality of fluorite synthetic stones, each fluorite synthetic stone comprising: a glass matrix comprising Ca, Si and O; and CaF2 crystals dispersed in the glass matrix at a concentration of at least about 70 wt.%.

[0051] A twenty-eighth aspect relates to the method according to the preceding aspect, wherein formulating the particulate mixture comprises: obtaining particulate material from a mining operation; determining a chemical content of the particulate material; and combining selected portions of the particulate material to form the particulate mixture.

[0052] A twenty-ninth aspect relates to the method according to any preceding aspect, wherein determining the chemical content of the particulate material includes determining the content of Ca, F and Si.

[0053] A thirtieth aspect relates to a method according to the preceding aspect, wherein determining the chemical content of the particulate material further comprises estimating the amount of CaF2, SiO2, CaO and / or CaCO3.

[0054] A thirty-first aspect relates to a method according to any preceding aspect, wherein determining the chemical content of the particulate material comprises performing x-ray fluorescence analysis on the particulate material.

[0055] A thirty-second aspect relates to a method according to any preceding aspect, further comprising adding one or more additional particulate materials to the particulate mixture after formulating the particulate mixture.

[0056] A thirty-third aspect relates to the method according to the preceding aspects, wherein the one or more additional particulate materials are selected from the group consisting of Al2O3 and MgO.

[0057] A thirty-fourth aspect relates to the method according to any preceding aspect, wherein the predetermined weight ratio is greater than 1.

[0058] A thirty-fifth aspect relates to the method according to any preceding aspect, wherein the predetermined weight ratio is about 2:1 to about 4:1.

[0059] A thirty-sixth aspect relates to the method according to any preceding aspect, wherein the predetermined weight ratio is less than 1.

[0060] A thirty-seventh aspect relates to the method according to any preceding aspect, wherein preparing the aggregate comprises mixing a binder into the particle mixture, the binder being selected from the group consisting of an organic binder, an inorganic binder, and an aqueous binder.

[0061] A thirty-eighth aspect relates to the method according to the preceding aspects, wherein the binder comprises a sodium silicate solution (water glass).

[0062] A thirty-ninth aspect relates to the method according to any preceding aspect, wherein the binder is added in an amount of about 2 wt.% to about 10 wt.%, or about 5 wt.% to about 7 wt.%.

[0063] A fortieth aspect relates to the method according to any preceding aspect, wherein preparing the aggregate comprises granulation, compaction, extrusion, micronization and / or briquetting.

[0064] A forty-first aspect relates to the method according to any preceding aspect, further comprising drying the aggregate to increase green strength before heat treating the aggregate.

[0065] A 42nd aspect relates to the method according to any preceding aspect, wherein the drying comprises evaporating or curing the binder.

[0066] A forty-third aspect relates to the method according to any preceding aspect, wherein the aggregate is heat treated at a temperature of at least about 950°C or at least about 1000°C and / or not higher than about 1200°C.

[0067] A forty-fourth aspect relates to a method according to any preceding aspect, wherein the aggregate is heat treated for a duration of at least about 20 minutes, at least about 40 minutes, at least about 60 minutes and / or at most about 120 minutes.

[0068] A forty-fifth aspect relates to a method according to any of the preceding aspects, wherein the aggregate is heat treated until CaCO3, CaO and / or SiO2 crystals are no longer detectable by x-ray diffraction.

[0069] A forty-sixth aspect relates to the method according to any preceding aspect, wherein the heat treatment comprises furnace heating or microwave heating.

[0070] A forty-seventh aspect relates to the method according to the previous aspects, wherein the aggregate is embedded in a susceptor material before the microwave heating is performed.

[0071] Aspect 48 relates to a method according to any preceding aspect, wherein the glass matrix comprises one or more silicates and / or oxides.

[0072] A forty-ninth aspect relates to a method according to any of the preceding aspects, wherein the glass matrix comprises a Ca-Si-O compound selected from the group consisting of Ca2SiO3 and Ca2SiO4 (2CaO·SiO2).

[0073] A fiftieth aspect relates to a method according to any preceding aspect, wherein the glass matrix is ​​partially fluorinated.

[0074] A fifty-first aspect relates to the method according to any preceding aspect, wherein the glass matrix comprises free CaO at a concentration of less than about 1 wt.%.

[0075] A fifty-second aspect relates to a method according to any preceding aspect, wherein the CaF2 crystals have a linear dimension in a range of about 500 nm to about 500 microns.

[0076] A fifty-third aspect relates to the method according to the preceding aspect, wherein the linear dimension is in the range of about 1 micron to about 150 microns.

[0077] A fifty-fourth aspect relates to a method according to any preceding aspect, wherein the CaF2 crystals have a multimodal size distribution.

[0078] A fifty-fifth aspect relates to a method according to any of the preceding aspects, wherein each fluorite synthetic stone further comprises SiO2 crystals dispersed in the glass matrix.

[0079] A fifty-sixth aspect relates to a method according to any of the preceding aspects, wherein each fluorite synthetic stone further comprises Al2O3 crystals and / or MgO crystals dispersed in the glass matrix.

[0080] A fifty-seventh aspect relates to a method according to any preceding aspect, wherein the fluorite synthetic stone contains C at a concentration of less than about 1 wt.% and / or contains no C.

[0081] A fifty-eighth aspect relates to a method according to any of the preceding aspects, wherein the fluorite synthetic stone contains CaCO3 at a concentration of less than about 2 wt.% and / or contains no CaCO3.

[0082] A fifty-ninth aspect relates to a method according to any preceding aspect, wherein the fluorite synthetic stone contains S at a concentration of less than about 0.1 wt.% and / or contains no S.

[0083] A sixtieth aspect relates to a method according to any preceding aspect, wherein the fluorite synthetic stone contains P at a concentration of less than about 0.1 wt.% and / or contains no P.

[0084] A sixty-first aspect relates to a method according to any preceding aspect, wherein the fluorite synthetic stone does not contain a binder.

[0085] A sixty-second aspect relates to a method according to any of the preceding aspects, wherein the fluorite synthetic stone has a buoyancy of about 2.2 g / cm 3 About 3g / cm 3 density within the range of .

[0086] A sixty-third aspect relates to the method according to any of the preceding aspects, wherein the mass loss of the fluorite synthetic stone is about 7 wt.% or less after subjecting the fluorite synthetic stone to the drum test for 60 minutes.

[0087] A sixty-fourth aspect relates to a method according to any preceding aspect, wherein the fluorite synthetic stone withstands an average compressive force of at least about 1330N before failure.

[0088] A sixty-fifth aspect relates to the method according to any preceding aspect, wherein the fluorite synthetic stone exhibits a water absorption of no more than about 0.1 wt. % after six days in a humidity chamber (>90% relative humidity).

[0089] A sixty-sixth aspect relates to a method according to any preceding aspect, wherein the fluorite synthetic stone has a nominal size in the range of a few millimeters to a few centimeters.

[0090] Although the present invention has been described in considerable detail with reference to certain embodiments of the invention, other embodiments are possible without departing from the invention. Therefore, the spirit and scope of the appended claims should not be limited to the description of the preferred embodiments contained herein. All embodiments falling within the meaning of the claims, whether literally or in an equivalent sense, are intended to be included therein.

[0091] Furthermore, the advantages described above are not necessarily the only advantages of the present invention, and it is not necessarily expected that all of the described advantages will be achieved with every embodiment of the present invention.

Claims

1. A fluorite synthetic stone comprising: a glass matrix comprising Ca, Si and O and having a predetermined weight ratio of Ca to Si; and CaF2 crystals dispersed in the glass matrix at a concentration of at least about 70 wt.%.

2. The fluorite synthetic stone according to claim 1, wherein the predetermined weight ratio of Ca to Si is greater than 1, and / or wherein the predetermined weight ratio of Ca to Si is from about 2:1 to about 4:

1. 3 . The fluorite synthetic stone according to claim 1 , wherein the predetermined weight ratio of Ca to Si is less than 1. 4 .

4. The fluorite synthetic stone of claim 1, wherein the concentration is at least about 80 wt.%, at least about 90 wt.%, at least about 92 wt.%, or at least about 94 wt.%, and / or up to about 96 wt.%.

5. The fluorite synthetic stone according to claim 1, wherein the glass matrix comprises one or more silicates and / or oxides. 6 . The fluorite synthetic stone according to claim 5 , wherein the glass matrix contains a Ca—Si—O compound selected from the group consisting of Ca 2 SiO 3 and Ca 2 SiO 4 (2CaO·SiO 2 ).

7. The fluorite synthetic stone of claim 1, wherein the glass matrix is ​​partially fluorinated.

8. The fluorite synthetic stone of claim 1, comprising free CaO at a concentration of less than about 1 wt.%.

9. The fluorite synthetic stone of claim 1, wherein the CaF2 crystals have linear dimensions in the range of about 500 nm to about 500 microns.

10. The fluorite synthetic stone of claim 9, wherein the linear dimension is in the range of about 1 micron to about 150 microns.

11. The fluorite synthetic stone according to claim 1, wherein the CaF2 crystals have a multimodal size distribution.

12. The fluorite synthetic stone according to claim 1, further comprising SiO2 crystals dispersed in the glass matrix.

13. The fluorite synthetic stone according to claim 1, further comprising Al2O3 crystals and / or MgO crystals dispersed in the glass matrix.

14. The fluorite synthetic stone according to claim 1, comprising C at a concentration of less than about 1 wt.% and / or containing no C.

15. The fluorite synthetic stone of claim 1, comprising CaCO3 at a concentration of less than about 2 wt.% and / or being free of CaCO3.

16. The fluorite synthetic stone according to claim 1, comprising S at a concentration of less than about 0.1 wt.% and / or containing no S.

17. The fluorite synthetic stone according to claim 1, comprising P at a concentration of less than about 0.1 wt.% and / or containing no P. The fluorite synthetic stone according to claim 1 , which does not contain a binder.

19. The fluorite synthetic stone of claim 1 having a buoyancy of about 2.2 g / cm 3 About 3g / cm 3 density within the range of .

20. The fluorite synthetic stone according to claim 1, which has high wear resistance, wherein: After subjecting the sample of the fluorite synthetic stone to the drum test for 60 minutes, the mass loss of the sample was about 7 wt.% or less.

21. The fluorite synthetic stone of claim 1, which withstands an average compressive force of at least about 1330 N before failure.

22. The fluorite synthetic stone of claim 1, exhibiting a water absorption of no more than about 0.1 wt.% after six days in a humidity chamber (>90% relative humidity).

23. The fluorite synthetic stone of claim 1 having a nominal size in the range of a few millimeters to a few centimeters.

24. A method of using the fluorite synthetic stone according to claim 1, the method comprising: A plurality of the fluorite synthetic stones are added to a steelmaking furnace containing slag and molten steel.

25. The method of claim 24, wherein the addition of the fluorite synthetic stone reduces the viscosity of the slag.

26. The method of claim 24, wherein the addition of the fluorite synthetic stone increases the ability of the slag to remove sulfur from the molten steel.

27. A method for producing fluorite synthetic stone, the method comprising: A granular mixture is prepared, the granular mixture comprising: CaF2 crystals having a concentration of at least about 70 wt.%; and an excipient having a predetermined weight ratio of Ca to Si; preparing an aggregate from the particle mixture; and heat treating the aggregate to form a plurality of fluorite synthetic stones, each fluorite synthetic stone comprising: a glass matrix comprising Ca, Si and O; and CaF2 crystals dispersed in the glass matrix at a concentration of at least about 70 wt.%.

28. The method of claim 27, wherein formulating the particle mixture comprises: Obtaining granular material from mining operations; determining a chemical content of the particulate material; as well as Selected portions of the particulate materials are combined to form the particulate mixture.

29. The method of claim 28, wherein determining the chemical content of the particulate material comprises determining the content of Ca, F, and Si.

30. The method of claim 29, wherein determining the chemical content of the particulate material further comprises estimating the amount of CaF2, SiO2, CaO, and / or CaCO3.

31. The method of claim 28, wherein determining the chemical content of the particulate material comprises performing x-ray fluorescence analysis on the particulate material.

32. The method of claim 27, further comprising adding one or more additional particulate materials to the particulate mixture after formulating the particulate mixture.

33. The method of claim 32, wherein the one or more additional particulate materials are selected from the group consisting of Al2O3 and MgO.

34. The method of claim 27, wherein the predetermined weight ratio is greater than 1.

35. The method of claim 34, wherein the predetermined weight ratio is from about 2:1 to about 4:

1.

36. The method of claim 27, wherein the predetermined weight ratio is less than 1.

37. The method of claim 27, wherein preparing the aggregate comprises mixing a binder into the particulate mixture, the binder selected from the group consisting of an organic binder, an inorganic binder, and an aqueous binder.

38. The method of claim 37, wherein the binder comprises a sodium silicate solution (water glass).

39. The method of claim 37, wherein the binder is added in an amount of about 2 wt.% to about 10 wt.%, or about 5 wt.% to about 7 wt.%.

40. The method of claim 27, wherein preparing the aggregate comprises granulating, compacting, extruding, micronizing, and / or briquetting.

41. The method of claim 27, further comprising drying the aggregate to increase green strength prior to heat treating the aggregate.

42. The method of claim 41, wherein the drying comprises evaporating or curing the binder.

43. The method of claim 27, wherein the aggregate is heat treated at a temperature of at least about 950°C or at least about 1000°C and / or no greater than about 1200°C.

44. The method of claim 27, wherein the aggregate is heat treated for a duration of at least about 20 minutes, at least about 40 minutes, at least about 60 minutes, and / or at most about 120 minutes.

45. The method of claim 27, wherein the aggregate is heat treated until CaCO3, CaO and / or SiO2 crystals are no longer detectable by x-ray diffraction.

46. ​​The method of claim 27, wherein the thermal treatment comprises furnace heating or microwave heating.

47. The method of claim 46, wherein: Prior to said microwave heating, said aggregate is embedded in a susceptor material.

48. The method of claim 27, wherein the glass matrix comprises one or more silicates and / or oxides.

49. The method of claim 27, wherein the glass matrix comprises a Ca-Si-O compound selected from the group consisting of Ca2SiO3 and Ca2SiO4 (2CaO·SiO2).

50. The method of claim 27, wherein the glass matrix is ​​partially fluorinated.

51. The method of claim 27, wherein the glass matrix comprises free CaO at a concentration of less than about 1 wt.%.

52. The method of claim 27, wherein the CaF2 crystals have linear dimensions in the range of about 500 nm to about 500 microns.

53. The method of claim 52, wherein the linear dimension is in the range of about 1 micron to about 150 microns.

54. The method of claim 27, wherein the CaF2 crystals have a multimodal size distribution.

55. The method of claim 27, wherein each fluorite synthetic stone further comprises SiO2 crystals dispersed in the glass matrix.

56. The method of claim 27, wherein each fluorite synthetic stone further comprises Al2O3 crystals and / or MgO crystals dispersed in the glass matrix.

57. The method of claim 27, wherein the fluorite synthetic stone comprises C at a concentration of less than about 1 wt.% and / or is free of C.

58. The method of claim 27, wherein the fluorite synthetic stone comprises CaCO3 at a concentration of less than about 2 wt.% and / or is free of CaCO3.

59. The method of claim 27, wherein the fluorite synthetic stone comprises S at a concentration of less than about 0.1 wt.% and / or is free of S.

60. The method of claim 27, wherein the fluorite synthetic stone comprises P at a concentration of less than about 0.1 wt.% and / or is free of P.

61. The method of claim 27, wherein the fluorite synthetic stone is binder-free.

62. The method of claim 27, wherein the fluorite synthetic stone has a buoyancy of about 2.2 g / cm 3 About 3g / cm 3 density within the range of .

63. The method of claim 27, wherein: After subjecting the fluorite synthetic stone to the drum test for 60 minutes, the mass loss of the fluorite synthetic stone is about 7 wt.% or less.

64. The method of claim 27, wherein the fluorite synthetic stone withstands an average compressive force of at least about 1330 N before failure.

65. The method of claim 27, wherein the fluorite synthetic stone exhibits no more than about 0.1 wt. % water absorption after six days in a humidity chamber (>90% relative humidity).

66. The method of claim 27, wherein the fluorite synthetic stone has a nominal size in the range of a few millimeters to a few centimeters.